APPLICATION OF CONFORMAL FIELD THEORY ON ELECTRON INTERACTION IN ONE DIMENSIONAL QUANTUM SYSTEMS - Hamim Zaidan (NIM 202 05 017), Andi
Abstract : At this thesis we will study behavior of electron in one dimensional quantum system especially interaction between electrons. Because Fermi liquid model breakdown and can no longer be applied in one dimensional quantum systems so we using Tomonaga-Luttinger Liquid (TLL) and its bosonization technique. Formulation of TLL in this thesis done by using conformal field theory. In conformal field theory TLL can be formulate using Gaussian model (c = 1) which describe about free boson. Determination of conformal dimension or conformal weight, central charge and correlation function which applicable to determine thermodynamics and electrical property from material can be done by using finite